EKSTRAKSI DIGITAL SURFACE MODEL (DSM) DARI DATA UNMANNED AERIAL VEHICLE (UAV) BERBASIS POINT CLOUD - Laksana, Indra; Suharyadi, R; Hadi, M Pramono (UI Scholars Hub, 2019)
Data acquisition using unmanned aircraft is increasingly being done. This study models elevation data from field measurements using unmanned aircraft. The purpose of this study: (1) to test the ability of unmanned aircraft to acquire elevation data, and (2) to compare elevation data if added point cloud data and bathymetry measurement data. The processing method using point cloud data is done by first matching key points. Matching key points links all aerial photography results to forming a single unit area that has been photographed. Next, a tie point is carried out in the area formed from matching key points. Tie points function as data correction when unmanned aircraft take data. Corrected aerial photos are then processed to obtain point cloud data. Point cloud is useful as orthophoto compiler data and Digital Surface Model (DSM) data. Point cloud data processing to produce DSM is done using Pix4D and Agisoft photoscan software. The results obtained showed that there was an increase in DSM capabilities when point cloud data was added to the tie point data and bathymetry measurement data. So, it can be concluded that data acquisition using unmanned aircraft is able to produce reliable data. Besides being reliable, data acquisition with unmanned aircraft is cheaper compared to data acquisition with aerial photography.